2005
DOI: 10.1042/bj20051257
|View full text |Cite
|
Sign up to set email alerts
|

Refolding of Escherichia coli outer membrane protein F in detergent creates LPS-free trimers and asymmetric dimers

Abstract: The Escherichia coli OmpF (outer-membrane protein F; matrix porin) is a homotrimeric beta-barrel and a member of the bacterial porin superfamily. It is the best characterized porin protein, but has resisted attempts to refold it efficiently in vitro. In the present paper, we report the discovery of detergent-based folding conditions, including dodecylglucoside, which can create pure samples of trimeric OmpF. Whereas outer membrane LPS (lipopolysaccharide) is clearly required for in vivo folding, the artificial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
38
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 44 publications
8
38
0
Order By: Relevance
“…Mesophilic proteins with T m values above 45°C are generally considered to be thermostable (70,71); all of the proteins studied herein met this criterion. Of note, the T m for OmpF is in close agreement with published values determined by both CD and differential scanning calorimetry (72). Each curve shows a sharp unfolding transition, indicating a two-state thermal unfolding, all of which were irreversible upon cooling from 90 set of experiments, we examined TprC C folded in DDM.…”
Section: Divergent Secondary Structures Of the Mosp N -And Mospsupporting
confidence: 68%
“…Mesophilic proteins with T m values above 45°C are generally considered to be thermostable (70,71); all of the proteins studied herein met this criterion. Of note, the T m for OmpF is in close agreement with published values determined by both CD and differential scanning calorimetry (72). Each curve shows a sharp unfolding transition, indicating a two-state thermal unfolding, all of which were irreversible upon cooling from 90 set of experiments, we examined TprC C folded in DDM.…”
Section: Divergent Secondary Structures Of the Mosp N -And Mospsupporting
confidence: 68%
“…OmpF trimers show identical structural and electrophysiological properties to those that folded in vivo in the presence of LPS in the OM (17,18).…”
mentioning
confidence: 79%
“…Here we provide support for these observations by showing that the successful in vivo OM biogenesis of OmpF requires the presence of an intact LPS B site at the periphery of the trimer. By contrast, the successful production of functional LPS-free OmpF by folding into detergent micelles suggested that LPS was not an essential component for OmpF in vitro (17,47). OMP biogenesis is mediated by the BAM complex, which accepts unfolded proteins from periplasmic chaperones (48) and mediates the formation of β-barrels in the OM via a mechanism that is not yet well-understood (49)(50)(51).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refolding of porins from inclusion bodies (IBs) and their structure determination was successful in the case of Rhodopseudomonas blastica porin (Schmid et al, 1996) and OpCA from Neisseria meningitidis (Prince et al, 2001) where the refolded proteins showed structural similarity to their native structures. OmpF from E. coli had been overexpressed and refolded in the presence of detergents (Miedema et al, 2004;Visudtiphole et al, 2005). However, this is the first report of crystallisation and structure determination of in vitro refolded OmpF from a human pathogen.…”
Section: Introductionmentioning
confidence: 94%